Addressing Anxiety Problems in Hospital Patients with Guided Imagery Therapy: A Systematic Review - Sulistiyawati, Sri; Muhith, Abdul; Mahyuvi, Tata (Journal of Applied Nursing and Health, 2024)
Background: Anxiety problems are often experienced by patients in hospitals due to various factors, such as medical conditions, medical procedures, or unfamiliar environments. One of the non-pharmacological interventions that has been widely studied to manage anxiety is guided imagery therapy. Objective: This systematic review aims to evaluate the effectiveness of guided imagery therapy in addressing anxiety problems in hospital patients. Methods: Literature searches were conducted on databases such as Google Scholar, Science Direct, and Pubmed. Article searches were carried out systematically from 2019-2024 using severalkeywords, namely "hemodialysis", or "guided imagery", or "anxiety", or "Patients in hospitals". Search for articles in English and Indonesia. Studies that met the inclusion criteria, i.e. experimental or quasi-experimental studies that evaluated the effects of guided imagery therapy on the anxiety levels of hospital patients, were further analysed. Data were extracted and compared to identify key findings. Results: : Studies show that guided imagery therapy can significantly lower anxiety levels in hospital patients, both before and after certain procedures. Positive effects were seen more pronounced in patients who underwent the intervention over several sessions compared to a single session. Additionally, patients reported improved relaxation, mood, and an overall more positive experience during the treatment period. Conclusion: : Guided imagery therapy is an effective and easy-to-apply approach to overcome anxiety in hospital patients. This intervention can be an additional option for health workers to improve the quality of health services, especially for patients with high levels of anxiety. Further studies are needed to explore the effects of these therapies in the context of the wider patient culture and population.